Stygmaty marginalizacji i wykluczenia w środowisku wielkiego miasta - na przykładzie Katowic - Świątkiewicz-Mośny, Maria (Studia Etnologiczne i Antropologiczne, 2010)
Stigmas are clear, irrational, emotional, provoking signs also thought of as a taint. People are marked with it. They mark the space. The source of stigma may be, according to Goffman, the origins, features of character or looks. The taint is not always connected with a deviant action, rule abuse and norm violation. Not each difference causes rejection; only the one which is noticed and unaccepted by the social audience. The mechanism of stigmatization in the big city environment goes from the space to its inhabitants. A marked space, forbidden district mark the inhabitants, sentencing them to rejection. Richness ghettos are formed next to poverty ghettos. This space marks as well. The very article discusses stigmas of the cultural foreignness, origins, differences because of illness or life style. The author makes an attempt to answer the question of the features the stigma must have to exist as such in the social awareness, especially among the inhabitants of the contemporary city. The results of the sociological studies conducted in Katowice allow for making a statement that the exclusion of marked people from city celebration, its conveniences and entertainments causes marginalization of individuals and whole groups. The big city space excludes the poor, the unemployed, the homeless, the sick, people of different looks, customs, traditions, natures. They become marked with the tint of otherness. What is also marked is the space of the part of the city inhabited by them in the awareness of its other inhabitants.